The Indian farmers' protest of 2020-2021
1 online resource
Keywords: "The Kisan Andolan or the Indian farmers' protest is one of the longest, biggest (and victorious) The Kisan Andolan or the Indian farmers' protest of 2020-21 is one of the longest, biggest (and victorious) social movements in the history of independent India. This book adopts a multi-disciplinary approach to contextualize the movement in the long run. It engages with the historical, social, and religious roots of the Andolan, examining what makes it so unique and transformative for Indian polity. It explores the (dis)continuities with previous resistance and contestation movements in India and globally, and debates the role so far of regional, religious and class-caste-gender identities. Through interviews, the volume also gives a specific voice and platform to grassroots activists and farmers from the movement. Part of the Social Movements and Transformative Dissent series, the book will appeal to scholars, activists and a wider audience interested in social movements and dissent politics in India and the Global South. It will also be of interest to students of economics, political science, anthropology, sociology, government, agrarian studies, Sikh and Punjab studies, politics, international relations, and diaspora studies"--